Formulation Development and Statistical Optimization of Ivabradine Hydrochloride Floating Pulsatile Microspheres Using Response Surface Methodology - Tubati, Vani Prasanna (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The objective of this work is to develop floating pulsatile microspheres of ivabradine Hydrochloride and statistical optimization using software based response surface methodology. Materials and Methods: The microspheres were prepared by nonaqueous solvent evaporation method in which three process variables were of utmost importance such as stirring speed, stirring time, and polymer concentration. The desired responses were % entrapment efficiency, % of buoyancy, and %DE at 20 min of microspheres. Optimization was done by fitting experimental data to the software program (Minitab). Obtained microspheres were subjected to different evaluation parameters which are essential in the development of the dosage form. Results and Discussion: The optimized batch of formulation showed satisfactory drug entrapment efficiency of 88.56 ± 1.12, % of buoyancy of 91.42 ± 1.09, and %DE at 20 min of 64.4 ± 0.36. Scanning electron microscopy analysis revealed that particles were spherical with smooth surface. Particles were free flowing and its average particle size 794 ± 1.43 μm. The developed optimized batch of microspheres maintained lag phase during floating in acidic medium (simulated gastric fluid) for 5 h followed by pulsatile release of ivabradine HCl within 30 min in phosphate buffer PH 7.4 (Simulated intestinal fluid). Fourier transform infrared spectroscopy and differential scanning calorimetry studies revealed that there was no interaction between ivabradine HCl and Eudragit S100. Conclusion: Ivabradine HCl floating pulsatile microspheres were successfully made using response surface methodology.